THE RELATIONSHIP BETWEEN UNDERNUTRITION STATUS AND PNEUMONIA INCIDENCE AMONG UNDER-FIVE CHILDREN IN INDONESIA: AN ECOLOGICAL STUDY - Talitha Nadhira Faza (Fakultas Ilmu Kesehatan, Kedokteran dan Ilmu Alam (FIKKIA), Universitas Airlangga, 2026)
Background: Pneumonia is one of the most prevalent infectious diseases and significantly contributes to children under-five’s mortality in East Java in 2021-2023. Pneumonia incidence among children under-five is caused by various factors, one of which is nutritional status which can affect the body's immune system and susceptibility to infection. Purpose: This study aimed to examine the relationship between undernutrition status and Pneumonia incidence among children under-five in East Java in 2021, 2022, and 2023. Methods: An ecological study with a descriptive and analytical approach through population correlation was used. Secondary data were retrieved from the East Java Provincial Health Profile for 2021, 2022, and 2023. The QGIS (Quantum Geographic Information System) software was used to map the distribution of undernutrition status and Pneumonia Incidence among children under-five in East Java in 2021, 2022, and 2023. The Spearman correlation test was also used to evaluate the relationship between undernutrition status and Pneumonia incidence in East Java in 2021, 2022, and 2023. Results: The results of the study revealed a significant relationship between undernutrition status and Pneumonia incidence among children under-five in East Java for all three years, with p-values of 0.002, 0.000, and 0.000, respectively (p values <α = 0.05). Conclusion: This study demonstrates a significant relationship between undernutrition status and Pneumonia incidence among children under-five in East Java in 2021, 2022, and 2023.